Hydrodynamic connectivity and potential oil pollution exposure of Marine Protected Areas: Implications for coastal management in Senegal - Issa Ba; Bruno Blanke; Siny Ndoye; Bamol Ali Sow; Patrice Bellec; Martial Boutet; Birane Ndom (Ocean & Coastal Management, 2026)

Modeling the convergence of buoyant debris in the Indian Ocean: Insights from surface drifter trajectories and Lagrangian simulations - Gaël Chauchadis; Christophe Maes; Bruno Blanke; Xavier Carton (Marine Pollution Bulletin, 2026)

Reconstructing monthly 20$$^th$$ century salinity fields using a data-driven method and Argo data - Erwan Oulhen; Nicolas Kolodziejczyk; Pierre Tandeo; Bruno Blanke; Florian Sévellec (Ocean Dynamics, 2025)

Sensitivity of gyre-scale marine connectivity estimates to fine-scale circulation - Saeed Hariri; Sabrina Speich; Bruno Blanke; Marina Lévy (Ocean Science, 2023)
We investigated the connectivity properties of an idealized western boundary current system separating two ocean gyres, where the flow is characterized by a well-defined mean circulation as well as energetic fine-scale features (i.e., mesoscale and submesoscale currents). We used a time-evolving 3D flow field from a high-resolution (HR-3D) ocean model of this system. In order to evaluate the role of the fine scales in connectivity estimates, we computed Lagrangian trajectories in three different ways: using the HR-3D flow, using the same flow but filtered on a coarse-resolution grid (CR-3D), and using the surface layer flow only (HR-SL). We examined connectivity between the two gyres along the western boundary current and across it by using and comparing different metrics, such as minimum and averaged values of transit time between 16 key sites, arrival depths, and probability density functions of transit times. We find that when the fine-scale flow is resolved, the numerical particles connect pairs of sites faster (between 100 to 300 d) than when it is absent. This is particularly true for sites that are along and near the jets separating the two gyres. Moreover, the connectivity is facilitated when 3D instead of surface currents are resolved. Finally, our results emphasize that ocean connectivity is 3D and not 2D and that assessing connectivity properties using climatologies or low-resolution velocity fields yields strongly biased estimates.

Influence of waves on the three-dimensional distribution of plastic in the ocean - Raphaël Bajon; Thierry Huck; Nicolas Grima; Christophe Maes; Bruno Blanke; Camille Richon; Xavier Couvelard (Marine Pollution Bulletin, 2023)

Eddy properties in the Southern California Current System - Fanny Chenillat; Peter J. S. Franks; Xavier Capet; Pascal Rivière; Nicolas Grima; Bruno Blanke; Vincent Combes (Ocean Dynamics, 2018)

Role of fronts in the formation of Arabian Sea barrier layers during summer monsoon - Clément de Boyer Montégut; Fabien Durand; Romain Bourdallé-Badie; Bruno Blanke (Ocean Dynamics, 2014)

Improvement in air–sea flux estimates derived from satellite observations - Abderrahim Bentamy; Semyon A. Grodsky; Kristina Katsaros; Alberto M. Mestas-Nuñez; Bruno Blanke; Fabien Desbiolles (International Journal of Remote Sensing, 2013)

How fast can the European eel ( Anguilla anguilla ) larvae cross the Atlantic Ocean? - SYLVAIN BONHOMMEAU; BRUNO BLANKE; ANNE‐MARIE TRÉGUIER; NICOLAS GRIMA; ETIENNE RIVOT; YOUEN VERMARD; ERIC GREINER; OLIVIER LE PAPE (Fisheries Oceanography, 2009)
The migration duration of European eel ( Anguilla anguilla ) larvae (leptocephali) from the spawning areas in the Sargasso Sea to the European continental shelf remains highly controversial, with estimates varying from 6 months to more than 2 yr. We estimated the fastest migration period and the shortest distance travelled by eel larvae by simulating Lagrangian particles released in the Sargasso Sea and by simulating a range of larval behaviours (fixed‐depth drift, vertical diurnal migration and active‐depth selection to maximize current velocity). This enabled us to compute (i) a passive drift speed, and (ii) a hypothetic swimming speed needed for European eel larvae to cross the Atlantic in 6 months (i.e., the migration duration estimated from otolith daily growth increments). Our results show that the minimum travel time for an eel larva that is passively drifting was 10 months and 3 days. Active behaviours (vertical diurnal migration and rheotaxis) paradoxically increased the migration period. We found that for leptocephali to cross the Atlantic Ocean in 6 months, they would need to swim a minimum of 3.4 body lengths per second for 8200 km. No larvae have been observed with such swimming capabilities. These results provide evidence that leptocephali cannot cross the Atlantic in 6 months.

Water mass transformation along the Indonesian throughflow in an OGCM - Ariane Koch-Larrouy; Gurvan Madec; Bruno Blanke; Robert Molcard (Ocean Dynamics, 2008)

High-resolution atmospheric forcing for regional oceanic model: the Iroise Sea - Héloïse Muller; Franck Dumas; Bruno Blanke; Vincent Mariette (Ocean Dynamics, 2007)

Displacements and transformations of nitrate-rich and nitrate-poor water masses in the tropical Pacific during the 1997 El Niño - Marie-Helene Radenac; Yves Dandonneau; Bruno Blanke (Ocean Dynamics, 2005)